Struktur Otak dan Keberfungsiannya pada Anak dengan Gangguan Spektrum Autis: Kajian Neuropsikologi - Nurussakinah - Daulay (Buletin Psikologi, 2017)
The purpose of this article is to understand the basic neuroanatomy of the brain and the neurodevelopmental characteristics of children with autism spectrum disorders. Children with autism spectrum disorders are children with complex developmental disorders, based on a neuropsychological approach, a disorder experienced by a child with autism due to abnormalities in the structure and biochemistry of the brain, as well as the interference in integrating sensory information received by the environment. Disturbances in the sensory process include how to obtain sensory information (sensory procesing), how to process the information (sensory procesing), and how to move the muscles and perform a series of movements in response to sensory stimuli received.